Legionella feeleii: Ubiquitous Pathogen in the Environment and Causative Agent of Pneumonia - Vaccaro, Lucianna; Gomes, Thiago Santos; Izquierdo, Fernando; Magnet, Angela; Llorens Berzosa, Sergio; Ollero, Dolores; Salso, Santiago; Alhambra, Almudena; Gómez, Carmen; López Cano, María; Pelaz, Carmen; Bellido Samaniego, Beatriz; et al. (Frontiers in Microbiology, 2021)
L. feeleii is one of the most frequent Legionella species isolated from natural pools of the central region of Spain. This study aimed to evaluate its ecology and to identify this Legionella species as a respiratory pathogen. A PCR assay for detecting the L. feeleii mip gene was developed to identify it in clinical and environmental samples. Culture and PCR were performed in environmental samples from four drinking water treatment plants (DWTPs). Free L. feeleii was only detected in raw water samples (3.4%), while L. feeleii as an Acanthamoeba endosymbiont was found in 30.7% of raw water, 11.5% of decanter biofilm, and 32% of finished water samples. Therefore, Acanthamoeba spp. plays an essential role in the multiplication, persistence, and spread of Legionella species in the environment. The first case of Legionnaires' disease caused by L. feeleii in Spain is described in this study. The case was diagnosed in an older woman through PCR and sequencing from urine and sputum samples. A respiratory infection could be linked with health care procedures, and the patient presented several risk factors (age, insulin-dependent diabetes, and heart disease). The detection of non-L. pneumophila, such as L. feeleii, is a factor that must be considered when establishing or reviewing measures for the control and prevention of legionellosis.